Sex Differences in the Performance of 7–12 Year Olds on a Mental Rotation Task and the Relation With Arithmetic Performance - van Tetering, Marleen; van der Donk, Marthe; de Groot, Renate Helena Maria; Jolles, Jelle (Frontiers in Psychology, 2019)
This study evaluates boy-girl differences in 3D mental rotation in schoolchildren aged 7-12 years and the relation to arithmetic performance. A dedicated new task was developed: The Mental Rotation Task – Children (MRT-C). This task was applied to a large sample of 729 children. At the age of 7- to 9-years, a sex difference was found in the number of correct judgments made on the MRT-C. Boys performed better than girls. A closer look at the distribution of boys and girls in this age group showed that boys were overrepresented in the top performance quartile, whereas girls were overrepresented in the lowest performance quartile. A second finding was that higher mental rotation performance was significantly correlated to better mathematical achievement. This finding was done for boys, but not for girls. This correlation underscores the important role that spatial processing plays in mathematical achievement and has implications for school practice.